A Survey on Converter Types and Energy Sources Used in Fuel Cell Electric Vehicles - Yildirim, Merve; Yilmaz, Bugra (Ieee, 2024)
In this paper, DC/DC converter types and energy sources including Battery (B), Ultracapacitor (UC), Supercapacitor (SC), and Fuel Cell (FC) used in Fuel Cell Electric Vehicles (FCEVs) are searched. Two type DC/DC converters are examined. While type 1 converter has lower voltage gain, higher current ripple, the voltage gain of type 2 with a capacitor clamped and FC lifespan are high. Furthermore, voltage stresses on semiconductors of the type 2 are also lower than type 1. For this reason, type 2 converter can be chosen for the FCEVs. The other topic handled in this study is the energy sources. Some features which are high power and energy densities, long lifespan, low operating temperature ranges, fast charge and discharge are expected from the energy sources to be used in the FCEVs. While the UCs meet these properties compared to the Bs, the energy density of them is low and the production cost is high. This limits the use of it in the FCEVs. The SCs can store the energy per unit compared to the UCs. This provide an advantage for long-term energy storage applications. However, the operating temperature ranges of them are limited compared to the UCs. The FCs offer high energy density and continuous operation but some challenges related to fuel availability and complexity. The choice between the FC and SC depends on the specific requirements of the application, including power and energy demands, operating conditions, and cost considerations. According to road conditions especially on a negative sloping road, recovering the energy by the regenerative braking is quite hard in the FCEVs with only FC. Hence, a FC/SC hybrid system can be preferred for providing a higher power density than the batteries.
5th International Conference on Clean and Green Energy Engineering-CGEE-Annual -- AUG 24-26, 2024 -- Izmir, TURKIYE
Keywords: electric vehicle; PEM fuel cell; DC/DC converter; energy sources